Glucose Concentration and Streptomycin Alter In Vitro Muscle Function and Metabolism. Issue 6 (June 2015) - Khodabukus, Alastair; Baar, Keith
<x xml:space="preserve">Abstract</x> Cell culture conditions can vary between laboratories and have been optimised for 2D cell culture. In this study, engineered muscle was cultured in 5.5 mM low glucose (LG) or 25 mM high glucose (HG) and in the absence or presence (+S) of streptomycin and the effect on C2C12 tissue‐engineered muscle function and metabolism was determined. Following 2 weeks differentiation, streptomycin (3‐fold) and LG (0.5‐fold) significantly decreased force generation. LG and/or streptomycin resulted in upward and leftward shifts in the force‐frequency curve and slowed time‐to‐peak tension and half‐relaxation time. Despite changes in contractile dynamics, no change in myosin isoform was detected. Instead, changes in troponin isoform, calcium sequestering proteins (CSQ and parvalbumin) and the calcium uptake protein SERCA predicted the changes in contractile dynamics. Culturing in LG and/or streptomycin resulted in increased fatigue resistance despite no change in the mitochondrial enzymes SDH, ATPsynthase and cytochrome C. However, LG resulted in increases in the β‐oxidation enzymes LCAD and VLCAD and the fatty acid transporter CPT‐1, indicative of a greater capacity for fat oxidation. In contrast, HG resulted in increased GLUT4 content and the glycolytic enzyme PFK, indicative of a more glycolytic phenotype. These data suggest that streptomycin has negative effects on force generation and that glucose can be used to shift engineered muscle phenotype via changes in calcium‐handling and metabolic proteins. J. Cell. Physiol. 230: 1226–1234, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company